Micro-CT 3D analysis: As an Alternative Diagnosis Tool for Measuring Growth and Development of Cranium - Wahyuni Dyah Parmasari; I Gusti Aju Wahju Ardani; Ida Bagus Narmada; Alexander Patera Nugraha; Ramadhan Hardani Putra; Fourier Dzar Eljabbar Latief; Fahrisah Nurfadeliah Bahraini (Jurnal Kesehatan Gigi, 2026)
In this study, the cranium of adult rats was used to examine the craniofacial anatomical markers of rats (Rattus Novergicus). This analysis helps determine key points for diagnosis. Markers on the rat skull were determined to establish measurements at two specific points. One way to validate craniofacial growth is to use Micro-Computed Tomography (micro-CT) as a marker of craniofacial growth by looking at craniofacial differences before and after a certain time. Micro-CT as an alternative diagnostic tool, especially for difficult surface areas to reach or measure. Sample analysis was performed and measured with the DataViewer Application version 1.6.0.0 64-bit. CTVox version-3.3.1 64-bit is used to display 3D visuals. After adjusting the data range, the reconstruction results are 30-255 (color range 0-255). The soft tissue of lower density is reduced to expose the hard tissue fully. The machine used is the Bruker SkyScan-1173 High Energy Micro-CT. Determination of the growth of the cranium in mice can be seen at the dorsal suture, Conca nasalis, and sphenoid base (cranial base). The uneven surface of the skull makes manual measurements difficult and impossible. However, this micro-CT method makes determining landmark points more detailed and has high accuracy or validity. This makes craniofacial geometric measurements more accurate and measurable. Micro-CT is an alternative diagnostic tool for measuring cranial growth in Rattus Novergicus, which cannot be achieved with 2D x-ray methods.